2012
DOI: 10.1158/0008-5472.can-11-0943
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pioneering Factor and Hormone Receptor Cooperative Pathways to Suppress Tumor Progression

Abstract: Nuclear receptors and pioneer factors drive the development and progression of prostate cancer. In this disease, aggressive disease phenotypes and hormone therapy failures result from resurgent activity of androgen receptor (AR) and the upregulation of coactivator protein p300 and pioneer factors (e.g. GATA2 and FOXA1). Thus, a major current emphasis in the field is to identify mechanisms by which castrate-resistant AR activity and pioneer factor function can be combinatorially suppressed. Here we show that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…In particular, restricted histone acetylation has been shown to inhibit the accessibility of chromatin to the AR by attenuating recruitment of the pioneering factor GATA2 [39]. The AR itself is also acetylated, a modification that increases its stability [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, restricted histone acetylation has been shown to inhibit the accessibility of chromatin to the AR by attenuating recruitment of the pioneering factor GATA2 [39]. The AR itself is also acetylated, a modification that increases its stability [73].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, acetyl-CoA promotes global histone acetylation and expression of pro-proliferative gene expression in cancer cells [15, 17, 38], although the underlying mechanisms of gene regulation by acetyl-CoA are not fully clear. Histone acetylation has been shown to be important for AR recruitment to chromatin and transcriptional activity [39]. Thus, elevated production of nuclear-cytoplasmic acetyl-CoA may support prostate tumor growth through both lipid metabolism and gene regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Another well-studied agent for KAT inhibition is curcumin – which is notable as a component of the spice turmeric, and has been implicated as an anticancer agent for decades (141) . In vitro use of curcumin in prostate lines has resulted in decreased AR activity in both androgen-dependent as well as castration-resistant PCa cells (142) . Despite this, the ubiquitous expression of KATs such as CBP and p300, and their importance in normal tissue as well as cancer cells severely limit the therapeutic window in which to treat patients.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies on several prostate cancer cell lines conducted by Shah S et al suggested that curcumin suppressed p300 and CBP occupancy at androgen receptor (AR) functional sites by decreasing the association of histone acetylation and pioneer factors, which resulted in the inhibition of AR residence and downstream target gene expression. They further verified the role of curcumin as a HAT inhibitor by using HDAC inhibitors, finding that the effects of curcumin on AR activity were reversed [133]. Another study on the human prostate cancer cell line LNCaP indicated that although the total HDAC activity was suppressed upon treatment with curcumin probably due to the decrease of HDAC8 expression, the expression of HDAC1, HDAC4, HDAC5 and HDAC8 were increased [134].…”
Section: Regulation Of Nutrients On Histone Modification In Cancermentioning
confidence: 95%